Magnetic susceptibility and heavy metals contamination in agricultural soil of Kopargaon area, Ahmadnagar District, Maharashtra, India - Patil, S. N.; Deshpande, A. V.; Varade, A. M.; Diwate, Pranaya; Kokoreva, A. A.; Golekar, R. B.; Gawali, P. B. (My University, 2022)
The objective of this work is to investigate the suitability of such measurements for indicating heavy metal contamination. Magnetic susceptibility measurements were carried out of agricultural soil which was collected from 23 locations from Kopargaon area of Ahmadnagar district, Maharashtra State of India, using AGICO MFK1-FA multifunction frequency Kappabridge KLY4S with low frequency susceptibility (F1) 976 Hz and high frequency susceptibility (F2) 15,616 Hz. The magnetic susceptibility values at low frequency were observed ranging from 16.83 × 10–7 m3/kg−1 to 59.38 × 10–7 m3/kg−1, whereas at high frequency, magnetic susceptibility found ranged from 16.17 × 10–7 m3/kg−1 to 56.38 × 10–7 m3/kg−1. This significant magnetic enhancement is an indication of presence of ferromagnetic minerals in agricultural soil from the studied area. Heavy metals in soil samples were analyzed by using double beam atomic absorption spectrophotometer. The mean concentration of Mn (6.760 mg/kg) followed by Fe (3.929 mg/kg), Cu (2.284 mg/kg), Pb (1.328 mg/kg), Zn (0.936 mg/kg), Cd (0.682 mg/kg) and Ni (0.595 mg/kg) was observed. The evaluation of anthropogenic influence and contamination with trace elements in soil from study area was carried out using geoaccumulation index. Soil geoaccumulation index (Igeo) shows that maximum values of Fe (5.599) and least value of Cd (−0.976) were observed. The geoaccumulation class (Igeo class) sequence was observed to be Cd > Pb > Ni > Zn > Cu > Mn > Fe. The interpretation of the obtained field measurements and the laboratory analyzes indicates that Cd, Pb and Ni provide the potential risk, whilst the other heavy metals are in the safe limits.
Keywords: Soil; Magnetic susceptibility; Heavy metals contamination; Geoaccumulation index; Kopargaon area; Ahmadnagar District; Maharashtra; India